Mediating consumer financial disputes: Financial Industry Disputes Resolution Centre's unique house style - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2020)
The Financial Industry Disputes Resolution Centre (“FIDReC”) was established in August 2005 with the purpose of providing a low-cost avenue for consumers to resolve their disputes with financial institutions. This article seeks to outline the role of FIDReC and its processes and, at the same time, seeks to define the house style of mediation that has served FIDReC well over the years. This article also highlights some of the different techniques adopted by FIDReC mediators in the course of facilitating the mediation.